Physiological responses to water deficiency in bread wheat (Triticum aestivum L.) lines with genetically different leaf pubescence - S. V. Osipova; A. V. Rudikovskii; A. V. Permyakov; E. G. Rudikovskaya; M. D. Permyakova; V. V. Verkhoturov; T. A. Pshenichnikova (Вавиловский журнал генетики и селекции)
Studying the relationship between leaf pubescence and drought resistance is important for assessing Triticum aestivum L. genetic resources. The aim of the work was to assess resistance of common wheat genotypes with different composition and allelic state of genes that determine the leaf pubescence phenotype. We compared the drought resistance wheat variety Saratovskaya 29 (S29) with densely pubescent leaves, carrying the dominant alleles of the Hl1 and Hl3 genes, and two near isogenic lines, i: S29 hl1, hl3 and i: S29 Hl2aesp, with the introgression of the additional pubescence gene from diploid species Aegilops speltoides. Under controlled conditions of the climatic chamber, the photosynthetic pigments content, the activity of ascorbate-glutathione cycle enzymes and also the parameters of chlorophyll fluorescence used to assess the physiological state of the plants photosynthetic apparatus were studied in the leaves of S29 and the lines. Tolerance was evaluated using the comprehensive index D, calculated on the basis of the studied physiological characteristics. The recessive state of pubescence genes, as well as the introduction of the additional Hl2aesp gene, led to a 6-fold decrease in D. Under the water deficit influence, the fluorescence parameters profile changed in the lines, and the viability index decreased compared with S29. Under drought, the activity of ascorbate peroxidase, glutathione reductase and dehydroascorbate reductase in the line i: S29 hl1, hl3 decreased 1.9, 3.3 and 2.3 times, in the line i: S29 Hl2aesp it decreased 1.8, 3.6 and 1.8 times respectively, compared with S29. In a hydroponic greenhouse, line productivity was studied. Compared with S29, the thousand grains mass in the line i: S29 hl1, hl3 under water deficit was reduced. The productivity of the line i: S29 Hl2aesp was significantly reduced regardless of water supply conditions in comparison with S29. Presumably, the revealed effects are associated with violations of cross-regulatory interactions between the proteins of the trichome formation network and transcription factors that regulate plant growth and stress response.